The Company's Responsibility Regarding Unilated Termination That Impact On Workers' Rights Is Reviewed From Law No. 6 of 2023 Concerning Job Creation - Prayusti Sarah Simarmata; Martono Anggusti; Jinner Sidauruk (Dinasti Research, 2025)
Layoffs refer to the termination of the employment relationship between employers and workers, which can occur for various reasons. When an employment contract ends due to the expiration of the agreed-upon term, it typically does not cause problems for either party, as both are aware of the end date and can prepare for the change. However, layoffs resulting from disruptions or unforeseen circumstances have a significant impact on both parties, especially workers, who often hold a weaker economic position compared to employers. A key element of legal protection against unilateral layoffs is the presence of an effective conflict resolution mechanism. This study aims to examine the responsibility of companies in unilaterally terminating employees, focusing on their obligation to provide workers' rights and the implementation of these provisions under Law No. 6 of 2023. The research utilizes a normative legal approach with a focus on statutory regulations. Legal sources include the Employment Law as primary material, scientific literature and books as secondary sources, and dictionaries as tertiary materials. Data analysis was conducted qualitatively, drawing on theoretical studies involving legal principles, concepts, and rules.